BERBAGAI FAKTOR PENENTU PENYESUAIAN PSIKOLOGIS POSITIF PENYINTAS BENCANA PASCA BENCANA - Kartika Nur Fathiyah (Paradigma, 2012)
Post-disaster disaster survivors experience severeobstacles in his adjustment. Nevertheless, natural disaster ortrauma encountered in life is not entirely negative effect.Exposure below attempts to lay out the findings of researchthat actually proves that disaster survivors to be very powerful,very strong and can develop post-disaster. Factors thatdetermine so helpless disaster after disaster survivors includesocial support, personal reinforcement in the form of selfacceptance,self-management, and positive coping strategieswhich can all be sourced from local cultural values.Keywords : Post-disaster disaster, self-acceptance, selfmanagement,and positive coping strategies